Exploring cross-country externalities, viable resilience, and sustainability options for small-scale fishing communities in the tropics - Lee, Ming-An; Mammel, Mubarak; Matovu, Baker; Korowi, Louis George; Mondal, Biraj Kanti; Martins, Irene; Mahata, Sanjib; Sedanza, Mary Grace (Frontiers in Ocean Sustainability, 2025)
IntroductionSmall-scale fishing communities are important for the development of emerging economies, sustaining livelihoods, and global food systems. However, the increasing human-environmental pressures are threatening the provision of these sustainability benefits. Unfortunately, limited research has been undertaken to comparatively explore the increasing vulnerabilities among fisherfolk and how sustainable transformations could be achieved.MethodsA mixed methods approach involving participatory interactions with coastal fisherfolk and sourcing/analysis of data on ocean circulation patterns and sea surface temperature from 2000 to 2020 was utilized. Participatory interactions were conducted with 230 and 209 fisherfolk in India and Papua New Guinea, respectively, to understand the level of vulnerability and possible viable options that could foster coastal fisherfolk sustainability and sustainable development.Results and discussionSmall-scale fisherfolk reported shared commonalities, especially in the fisheries systems, activities, and vulnerabilities. There is gender-specific specialization in fishing activities. Fishing is a job that embodies unique socio-cultural identities. Fisherfolk's identity is protected using century-long fishing methods. Most fisherfolk, especially in Papua New Guinea, predominantly possess low formal education and utilize semi-modern fish preservation techniques. Social-demographic vulnerabilities are increasing, such as the aging population. The declining fishing population leads to unsustainable livelihood futures. The burden of securing household livelihood often falls on a single individual. Increased vulnerability has increased the use of unsustainable fishing practices. Ocean circulation patterns are becoming extreme in all locations. Ocean temperatures have increased by 2 OC from 2000. From 2018-2020, the Indian Ocean Dipole increased to almost 1. Sea surface temperatures are increasing along the northwest fishing coast of India. Sea surface temperatures in northern fishing zones of Papua New Guinea are reducing. Additionally, increasing illegal and exploitative fishing by distant fleets was reported. Fisherfolk are experiencing a socioeconomic identity crisis. Hard and soft measures, including community-based fisheries rights and licensing of fishing operations, are reported, although with mixed results. This calls for collaborative governance mechanisms that are flexible and integrate the fisherfolk communities. Six sustainable leverage points are co-identified and co-created that can enhance sustainable marine fisheries transformations. The leverage points incorporate critical marine social science and fisheries science theoretical and conceptual perspectives and narratives. By incorporating the key components of the leverage points, the possibilities of aligning sustainable fisheries targets to regional and global blue transformation programs in Indian and Papua New Guinea could be initiated. In regions with small-scale fishing communities, findings revealed that although building resilience is complex, due to increasing human-environmental pressures in fishing zones, collaborative actions, including the recognition of the value of conventional fisherfolk, indigenous communities, and fisherwomen inclusion are critical. This helps in creating voluntary actions on sustainable fishing practices, governance, and management. To further drive social-natural science sustainability research in vulnerable tropical fishing regions, emphasis should be placed on conducting research that engages/captures the perspectives of the vulnerable fisherfolk.